Islamic Values And Digital Health Communication Adoption: Theory Of Reasoned Action Study - Wahyuti, Tri; Sudarmanti, Rini (KOMUNIKA, 2025)
This study uses the Theory of Reasoned Action framework to examine Islamic values' influence on adopting digital health communication technology among Muslim patients in Indonesian private hospitals. Through a quantitative approach, 200 Muslim patients who had used digital health communication platforms in Jakarta's private hospitals were surveyed. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), the research found that Islamic values—particularly siddiq (honesty), tabligh (clear communication), amanah (trust), and fathanah (intelligence)—significantly influence patients' attitudes (β = 0.676, p < 0.001) and subjective norms (β = 0.762, p < 0.001) regarding digital health communication technology. These factors subsequently affect behavioral intentions and actual adoption behaviors. The study reveals that subjective norms exert a more substantial influence on behavioral intention (β = 0.462) than attitudes (β = 0.396), highlighting the collectivist nature of Indonesian society. The model demonstrates robust explanatory power for behavioral intention (R² = 0.592) and actual behavior (R² = 0.557), indicating that successful digital transformation in healthcare requires alignment with cultural and religious values. These findings provide crucial insights for healthcare providers to enhance patient engagement through culturally sensitive digital communication strategies in predominantly Muslim contexts.